2020
DOI: 10.1186/s13063-020-4185-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a multi-level intervention to reduce men’s perpetration of intimate partner violence: a cluster randomised controlled trial

Abstract: Background: Men's perpetration of intimate partner violence (IPV) limits gains in health and wellbeing for populations globally. Largely informal, rapidly expanding peri-urban settlements, with limited basic services such as electricity, have high prevalence rates of IPV. Evidence on how to reduce men's perpetration, change social norms and patriarchal attitudes within these settings is limited. Our cluster randomised controlled trial aimed to determine the effectiveness of the Sonke CHANGE intervention in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…16 Main outcomes for IPV In the main analysis, men in the CHANGE trial showed no difference in the cluster-level proportion past year physical IPV (diff=0.002, 95% CI=−0.07-0.08) or sexual IPV (diff=0.01, 95% CI=−0.04-0.06ß) at endline after adjusting for sociodemographic characteristics and baseline IPV perpetration. 20 Severe IPV followed a similar pattern (diff=0.01; 95% CI=−0.05-0.07).…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…16 Main outcomes for IPV In the main analysis, men in the CHANGE trial showed no difference in the cluster-level proportion past year physical IPV (diff=0.002, 95% CI=−0.07-0.08) or sexual IPV (diff=0.01, 95% CI=−0.04-0.06ß) at endline after adjusting for sociodemographic characteristics and baseline IPV perpetration. 20 Severe IPV followed a similar pattern (diff=0.01; 95% CI=−0.05-0.07).…”
Section: Methodsmentioning
confidence: 71%
“…In the Sonke CHANGE trial, there was a steep decrease in past year physical and/or sexual IPV in the intervention arm from 45.7% at baseline, to 39.0% midline and 26.9% at endline (though overall the intervention showed no impact because of similar patterns in the control arm 20 ). Two-thirds (66.0%) of men were in the flat-low trajectory, one-fifth (19.1%) were in the high decreasing trajectory and 14.8% were in the high slightly increasing trajectory (figure 2 and online supplementary table 1).…”
Section: Prevalence Of Ipv and Trajectories Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this analysis highlights the possibility that interventions may work to different extents for different sub-populations and may have differential impacts on primary versus secondary prevention. Prior subgroup analyses also suggest that interventions may work differently for perpetrators who were report low versus high levels of violence at baseline ( Christofides et al, 2020 ; Gibbs, Dunkle, et al, 2020 ). These results suggest that IPV prevention programs need to be tailored to suit the needs of different subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies have explored the differential impacts of IPV prevention programming on different categories of men. A study using latent class analysis found that the Sonke CHANGE intervention in South Africa may have been more effective at reducing IPV perpetration among men who were less violent and reported lower non-partner sexual violence perpetration as compared to anti-social and hypermasculine men who reported high levels of violence at baseline ( Christofides et al, 2020 ). Another study used group-based trajectory analyses to identify trajectories of violence perpetration among men enrolled in the intervention arms of three separate IPV prevention trials in Africa—the Sonke CHANGE trial in a peri-urban area of Johannesburg; the Stepping Stones/Creating Futures trial among young men in Durban; and the Indashykirwa trial among cohabiting couples in Rwanda.…”
Section: Introductionmentioning
confidence: 99%